Mobilität von Kindern. Stand der Forschung und planerische Konzepte - Scheiner, Joachim (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
Children’s travel behaviour has emerged as a research field in the past years that can hardly be overseen anymore, yet Germany has remained remarkably silent in this field. The motivations for this research are primarily in the increase in being driven at the expense of non-motorised and/or independent mobility of children. This trend has negative implications for the development and health of the children, and it raises problems in traffic safety, the environment and more. The paper gives an overview of the research field. It discusses research foci, methods, and factors that affect children’s mobility. What is more, it discusses the – rather scarce – practical literature and shows ways how to support non-motorised and/or independent mobility of children.
Keywords: Children‘s travel behaviour; Independent mobility; Travel mode choice; School trip; School transport